Effect of the concentrations of seminal plasma and aerobic or anaerobic condition on the motility of cooled equine semen - Yong-Soo Park; Jae-Hyuk Yang; Young-Jae Cho; Ok-Deuk Kang; Gil-Jae Cho (The Korean Society of Animal Reproduction and Biotechnology, 2018)
The purpose of this study was to investigate the effects of the concentration of seminal plasma in aerobic and anaerobic conditions on the total motility(TM) and the progressive motility(PM) of spermatozoa in long term preservation of cooled equine semen. We also examine the pregnancy rates after artificial insemination using fresh, cooled or frozen semen, and different durations of cooled-preserved equine semen. In the aerobic state of cooledpreserved semen, As the increase of preserved duration to 24h, 48h, 72h, and 96h, TM tended to decrease in each of different concentrations of formalin-containing experimental group, TM tended to decrease regardless of the concentrations of SP. In different concentrations of SP, TM of without seminal plasma(SP W/O) group tended to be higher than that of SP 20%, SP 33% and SP 50%, especially TM of SP W/O group was significantly higher than other groups at 96 h (p<0.05). PM was higher in the groups of SP W/O and SP 20% than in the groups of SP 33% and SP 50% from 24 h to 72 h in cooled-preservation, especially PM of SP W/O group was significantly higher than other groups at 96 h (p<0.05). In the anaerobic condition of cooled-preserved semen, the results of TM and PM at different concentrations of SP were similar to the results in the aerobic condition although there was a difference in the ratio. The pregnancy rates of fresh-cooled, cooled-preserved and frozen semen were 66.3%, 60.7% and 34.5%, respectively, and the pregnancy rate of frozen semen was the lowest. We also found that it is possible to pregnancy after artificial insemination using 72 h cooled-preserved equine semen. There was similar of the pregnancy rates in the different month from April to August.